Marine Invertebrate Natural Products for Anti-Inflammatory and Chronic Diseases. (31st December 2013) - Senthilkumar, Kalimuthu; Kim, Se-Kwon
Abstract : The marine environment represents a relatively available source of functional ingredients that can be applied to various aspects of food processing, storage, and fortification. Moreover, numerous marine invertebrates based compounds have biological activities and also interfere with the pathogenesis of diseases. Isolated compounds from marine invertebrates have been shown to pharmacological activities and are helpful for the invention and discovery of bioactive compounds, primarily for deadly diseases like cancer, acquired immunodeficiency syndrome (AIDS), osteoporosis, and so forth. Extensive research within the last decade has revealed that most chronic illnesses such as cancer, neurological diseases, diabetes, and autoimmune diseases exhibit dysregulation of multiple cell signaling pathways that have been linked to inflammation. On the basis of their bioactive properties, this review focuses on the potential use of marine invertebrate derived compounds on anti-inflammatory and some chronic diseases such as cardiovascular disease, osteoporosis, diabetes, HIV, and cancer.